IoT for Agricultural Innovation: Enhancing Robusta Coffee Seedling Growth in Controlled Environments with Intelligent Air Quality Control System (IAQCS) - Rosdiana, Eva; Ali, Fandyka Yufriza; Pristiwaningsih, Estin Roso; Purbaningtyas, Rani; Hartadi, Didit Rahmat; Utomo, Denny Trias (P3M Politeknik Negeri Jember, 2025)
Advancements in Internet of Things (IoT) technology have revolutionized agriculture by enabling real-time monitoring and automated environmental control to optimize crop growth. This study focuses on evaluating the impact of IoT implementation on greenhouse environmental stability and the growth of Robusta Coffee Clone BP 308 seedlings, emphasizing plant height and leaf count as key parameters. The IoT system incorporates DHT11/DHT22 sensors for temperature and humidity monitoring, soil pH sensors, and an ESP8266 WiFi module for data transmission to an IoT platform. Additionally, Fuzzy Logic algorithms were employed to analyze the data and regulate environmental conditions such as temperature and humidity automatically. The experimental design compared IoT-based systems with conventional methods in a controlled greenhouse environment. Results demonstrated that the IoT system significantly enhanced environmental stability, maintaining an average temperature of 26.59°C and humidity of 86.46%, compared to conventional systems with greater fluctuations of 28.43°C and 82.69%. This stability positively impacted seedling growth, with IoT-treated plants achieving significantly higher heights and leaf counts at weeks 3, 6, and 9. By week 9, IoT-treated seedlings averaged a height of 24.00 cm with 11.73 leaves, outperforming non-IoT seedlings, which reached only 14.07 cm with 8.27 leaves. These findings highlight IoT's potential to create optimal growth conditions, reduce environmental stress, and enhance photosynthetic efficiency. Furthermore, IoT's precision in managing resources supports sustainable agriculture, making it an essential tool for improving productivity and competitiveness, especially in coffee cultivation, a key commodity in Indonesia.